Effect of foliar spraying With some plant extracts on growth and production of tomatoes (Lycopersicum esculentum L.) in unheated greenhouses (Latakia University Journal -Biological Sciences Series, 2023)
The research was carried out in the village of Harison, Banias district, Tartous governorate, during the spring season in 2022 . The tomato hybrid ''Yusra'' was used in the study, and 6treatments of foliar spraying with licrice and garlic were studied with two concentrations (2,5 and 5 gł ) each of them in four replications for each treatment and at two concentration of according to the random block design. The results of the study showed that the treatments of foliar spraying with licorice and garlic with different concentrations were significantly superior to the control plants in the indicators of vegetative and fruiting growth and productivity, the largest number of fruits on the plant is garlic 5gł 37.94 fruits/ plant, and the highest yield per unit area is 19.8 kg/m . Foliar spraying treatments also gave an increase in the percentage of knotty flowers amounting to 95.92 % . gł , 95.18% when spraying garlic 2.5 gł , 95.13 when spraying Liquorice 2.5 gł .